BIOPOLITICS AND NECROPOLITICS IN THE AMAZON BY DALCÍDIO JURANDIR - das Chagas Lacerda, Oclécio (Seven Editora, 2025)
This text aims to investigate the thoughts and conduct of Eutanásio, a character in the novel Chove nos campos de Cachoeira, by Dalcídio Jurandir, in order to, based on the musings and contradictory attitudes of this literary figure, justify the presence of biopolitics and necropolitics in the social relations of the Amazon at the beginning of the 20th century. During this period, biopower was evident in the villages of a small town in the Amazon region, Marajó Island, manifesting itself not only in its preliminary form, with disciplinary mechanisms, but also in its globalizing configurations, such as disease control. Necropower can also be identified in the new form of occupation of Amazonian lands post-colonization, which resulted in the formation of large estates. DOI: https://doi.org/10.56238/sevened2025.029-047